Talent identification in elite gymnasts: Why body size is so important - Richards, J. (coachesinfo.com, 1999)
About tendencies and developments in (women) gymnastics according to body size and body shape. Summary: For optimal performance in gymnastics the following factors are important: - a small body - small steady increases in growth - high strength : weight ratio - training greater than 20 hours per week.